An Review on Occlusal Plane Analysis in Dentulous Patients - S. Chandrakala1, Ganesh Ramesh2 , Sanjna Nayar3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The position of the occlusal plane forms the basis for the ideal teeth arrangement. Incorrect records of theocclusal plane would hamper aesthetics, phonetics, and mastication. It may affect the stability of a completedenture and ultimately result in alveolar bone resorption.Because the term plane refers geometrically to a flatsurface, it is not entirely correct to describe the occlusal surface as following a true plane.The form of the occlusal plane is directly related to specific functional requirements. In addition to thealignment of teeth in relationship to the arc of closure for best resistance to loading, it should permit easeof access for positioning of the food on the occlusal surfaces. This article is a review of the simple methodsof analysing the occlusal plane in dentulous plane and correcting the occlusal problems in these patients.